A 0D-3D approach for numerical analysis of waste to energy plants: a case study. Issue 1 (April 2021) - Arpino, F.; Cortellessa, G.; Canale, L.; Dell'Isola, M.; Ficco, G.; Moretti, L.; Zuena, F.; Rinaldi, F.
Abstract: In this paper the authors present a 0D-3D approach for numerical modelling of a waste-to-energy plant located in Italy in different operating conditions. This innovative methodology combines a 0D lumped parameters model, able to describe the processes of solid and gaseous combustion and the heat transfer within the first radiant channel, with a detailed 3D CFD simulation of the thermo-fluid-dynamic field within the plant combustion chamber. Results from the 0D model allow the definition of input data and boundary conditions for detailed 3D CFD simulation of the thermo-fluid-dynamic field within the plant combustion chamber. In this way, the T2S temperature can be determined according to actual definition of European legislation. The developed numerical tool is generally applicable to any waste-to-energy plant, and is here applied for the characterization of different operating conditions of an Italian WTE plant. The analysis allows the verification of the constraints imposed by the European legislation on the temperature of the combustion products and the identification of any issues related to the plant operation. In order to demonstrate the performance of the proposed numerical modelling approach, in this paper the authors present and discuss the results obtained by applying the model to one day-averaged operating condition of a WTE plant in Italy. Input parameters are obtained from available measurements and numerical results are validated against experiments showing a good agreement. Data and results in this paper are presented in a normalized form for confidentiality.